Analisis Potret Pertanian di Kota Tuban Meliputi Tanaman Palawija, Perkebunan, Peternakan, Kehutanan, Perikanan - Ery Chusnul Aldi; Safira Aprilia Lukita; Muhammad Yasin (Pusat Riset dan Inovasi Nasional, 2023)
Agriculture plays an important role in food sustainability and security in Indonesia, including in the City of Tuban. The city has wide potential for the development of the agricultural sector, including crops, plantations, animal husbandry, forestry and fisheries. However, the limited information regarding the current situation of these sectors raises the need for in-depth analysis. This study aims to analyze the portrait of agriculture in the city of Malang with a focus on crops, plantations, animal husbandry, forestry, and fisheries. This analysis will provide insight into the current status, development potential, challenges and opportunities within these sectors. This research uses a qualitative approach by conducting field surveys, interviews with farmers, ranchers, fishermen, and other relevant stakeholders. The collected qualitative data were analyzed thematically to describe an overall picture of each agricultural sector. The results of the analysis show that the secondary crops sector has experienced positive growth, but still faces challenges in terms of access to markets and technology. Plantations have great potential in the development of superior commodities, but need to improve infrastructure and environmental sustainability. Livestock is experiencing rapid development, but faces problems in waste management and animal health. Forestry is faced with land expansion and forest restoration, while fisheries require steps to maintain the sustainability of fish resources. These findings provide important input for the local government and related stakeholders to develop a strategy for sustainable agricultural development in the City of Tuban. Efforts are needed to improve market access, strengthen infrastructure, improve waste management, improve animal health, and maintain the sustainability of fish resources. This analysis can also be the basis for further research and more effective policy planning in the agricultural sector in Tuban City.